INNV-02. MULTIFOCAL, DURABLE AND PATHOLOGICALLY-CONFIRMED BRAIN METASTASIS COMPLETE RESPONSE TO TRASTUZUMAB DERUXTECAN. (14th November 2022) - Tosi, Umberto; Moss, Nelson; Santomasso, Bianca; Beal, Kathryn; Modi, Shanu
Abstract: Antibody-based conjugates (ADCs) have transformed the treatment of Her2+ breast and other cancers. Unfortunately, the CNS remains a sanctuary site for many such patients in part due to differential activity of macromolecules across the blood-brain and blood-brain tumor barriers. Trastuzumab deruxtecan (T-DXd), a high-payload ADC, was recently found to improve the progression-free survival of Her2+ breast cancer patients compared with prior-generation trastuzumab emtansine, prompting us to evaluate this agent in a woman with CNS-only metastatic disease. T-DXd achieved complete response despite heavy pretreatment. Three persistent (and previously-irradiated) lesions were subsequently biopsy-proven to represent treatment effect. Response was durable through 7 months of treatment, with subsequent recurrence in the setting of treatment holiday; partial response was observed with drug rechallenge. Drug discontinuation was ultimately required due to concern for pulmonary toxicity. Our case suggests T-DXd is active in Her2+ breast cancer brain metastases and supports further prospective evaluation in randomized clinical trials.